The Impact of English-Only Instruction Policies in Indonesian Higher Education Institutions - Pangestu, Aditya (Pemuda Peduli Publikasi Insan Ilmiah, 2025)
Purpose: This study explores the impact of English-only instruction policies in Indonesian higher education, particularly how such policies are interpreted, implemented, and experienced by academic stakeholders. It examines the extent to which English-medium instruction (EMI) advances institutional goals of internationalization while addressing challenges in practice. Subjects and Methods: A qualitative approach was employed, involving in-depth interviews with faculty members, students, and administrators across multiple Indonesian universities. This method allowed for rich insights into stakeholders’ perceptions, experiences, and strategies in navigating English-only policies. Results: Findings indicate that English-only instruction policies are often implemented unevenly, generating fragmented practices across institutions. Students frequently report linguistic anxiety, reduced classroom participation, and a reliance on informal code-switching. Faculty and administrators highlight a gap between the symbolic appeal of English for global competitiveness and the limited pedagogical and institutional support available. The policy is thus perceived as more symbolic than functional, reflecting external benchmarks rather than educational priorities. Conclusions: The study emphasizes the need for context-sensitive, multilingual, and equity-oriented policies. Sustainable internationalization in higher education requires moving beyond rigid English-only mandates toward inclusive strategies that empower both educators and learners.